Development of a Stand-alone Solar Powered Bus Stop - Mohd Afzanizam, Mohd Rosli; Akop, Mohd Zaid; Mansor, Muhd Ridzuan; Sivarao, Subramonian (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2011)
This paper presents the development of a stand-alone solar photovoltaic (PV) system for bus stop at Universiti Teknikal Malaysia Melaka, Malaysia. The design intent for the bus stop was to provide lighting and information to the bus stop users using reliable renewable energy system as well as to promote green technology awareness to the university residences. The stand-alone PV system was designed to power two units of CFL lamps and an LED display unit installed at the bus stop. Five units of polycrystalline photovoltaic modules with 110W rating each and four deep cycle battery units were utilized to provide three days of autonomy period for system operation. A part from that, 15 degree of tilt angle was selected for PV module placement to provide optimum energy generation as well as self cleaning for the modules. After the bus stop structure construction, the PV system was installed and commissioned. Final results from the commissioning process showed that the system is able to operate successfully as per design requirement.